PERTENTANGAN KOMPILASI HUKUM ISLAM DENGAN PUTUSAN MA TENTANG WARIS BEDA AGAMA: STUDI KASUS No. 331 K/Ag/2018 - Firly, Firly Diana Putri; Ahmad Mas’ari; Adikza Nurul Islam; Yuni Harlina (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2025)
This study examines Supreme Court (SC) Decision No. 331/K/Ag/2018, which granted inheritance via a mandatory bequest to the non-Muslim husband of a deceased Muslim wife, contrasting with Islamic law requirements stipulating Muslim heirs. It analyzes the judges' rationale and provides an Islamic legal review of the decision. Employing descriptive qualitative library research, primary sources included the SC decision and the Compilation of Islamic Law (KHI), supplemented by secondary legal materials like books and journals. Data was gathered through relevant literature and analyzed using content analysis. Findings reveal: (1) The SC justified its ruling based on the harmonious and affectionate relationship between the wife (heir) and husband (decedent) during their marriage. (2) From an Islamic legal perspective, the decision to award a mandatory bequest to the non-Muslim husband is deemed inappropriate. The KHI and prevailing Islamic jurisprudence explicitly require Muslim faith for inheritance rights, and the mandatory bequest mechanism is not intended to circumvent this religious prohibition for non-Muslim heirs. The study concludes the SC decision conflicts with established Islamic inheritance principles.